2020
DOI: 10.1101/2020.12.27.424486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chirality of the mitotic spindle provides a mechanical response to forces and depends on microtubule motors and augmin

Abstract: Mechanical forces produced by motor proteins and microtubule dynamics within the mitotic spindle are crucial for the movement of chromosomes and their segregation into the emerging daughter cells. In addition to linear forces, rotational forces are present in the spindle, reflected in the left-handed twisted shapes of microtubule bundles that make the spindle chiral. However, the molecular origins of spindle chirality are unknown. Here we show that spindles are most twisted at the beginning of anaphase, and re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 80 publications
3
12
0
Order By: Relevance
“…Despite their importance to spindle architecture, when dynein and Eg5 are co-depleted, human spindles form as typical bipoles (Florian and Mayer, 2012;Tanenbaum et al, 2008;van Heesbeen et al, 2014). Similar phenomena have been reported in yeast, Drosophila, Xenopus laevis extract, and pig spindles when the homologous kinesin-5 and the dominant end-clustering motor (dynein or a kinesin-14) are inhibited (Ferenz et al, 2009;Mitchison et al, 2005;Rincon et al, 2017;Saunders and Hoyt, 1992;Sharp et al, 1999).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Despite their importance to spindle architecture, when dynein and Eg5 are co-depleted, human spindles form as typical bipoles (Florian and Mayer, 2012;Tanenbaum et al, 2008;van Heesbeen et al, 2014). Similar phenomena have been reported in yeast, Drosophila, Xenopus laevis extract, and pig spindles when the homologous kinesin-5 and the dominant end-clustering motor (dynein or a kinesin-14) are inhibited (Ferenz et al, 2009;Mitchison et al, 2005;Rincon et al, 2017;Saunders and Hoyt, 1992;Sharp et al, 1999).…”
Section: Introductionsupporting
confidence: 63%
“…We found that the kinesins Kif15 and HSET are both required to establish bipolarity ( Figure 1K; Movie S2). Partially depleting Kif15 in doubly inhibited spindles led to the formation of more monopoles (46%; Figures 1K, S1E, and S1F), consistent with its role in generating extensile stress (Sturgill and Ohi, 2013;Tanenbaum et al, 2009;van Heesbeen et al, 2014;Vanneste et al, 2009). Conversely, depleting HSET caused more spindles to remain turbulent (44%), indicating that it performs contractile minus end clustering.…”
Section: Results: Eg5 Inhibition Allows Turbulent Spindles To Recovermentioning
confidence: 52%
“…The spindle in Fig. 1 was imaged as described in Trupini c et al (18). Further examples of imaging both live and fixed cells for purpose of measuring twist can be found in Novak et al (17).…”
Section: Cell Lines and Microtubule Visualizationmentioning
confidence: 99%
“…The direction of the imaging is important for determining handedness of the twist (right-or left-handed twist). Examples of microscope settings for the purpose of imaging spindles for measuring twist can be found in Novak et al (17) and Trupini c et al (18).…”
Section: Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation